Fluid mechanics - Munson, Bruce Roy , 1940- (Singapore : Wiley, 2013)
Fundamentals of Fluid Mechanics offers comprehensive topical coverage, with varied examples and problems, application of visual component of fluid mechanics, and strong focus on effective learning. The text enables the gradual development of confidence in problem solving
1. Introduction -- 2. Fluid statics -- 3. Elementary fluid dynamics-the Bernoulli equation -- 4. Fluid kinematics -- 5. Finite control volume analysis -- 6. Differential analysis of fluid flow -- 7. Dimensional analysis, similitude, and modeling -- 8. Viscous flow in pipes -- 9. Flow over immersed bodies -- 10. Open-channel flow -- 11. Compressible flow -- 12. Turbomachines
Previous ed. published as: Fundamentals of fluid mechanics. Hoboken, N.J. : Wiley, 2009
Includes bibliographical references and index
Keywords: Fluid mechanics